Gauging Customer Sentiment Regarding Indonesian Islamic Digital Banks - Bawana, Tate Agape; Mansor, Fadillah; Noordin, Kamaruzaman (University of Darusssalam Gontor, 2024)
The convergence of established Islamic finance and digital platforms has led to the emergence of Islamic digital banking. This study examines the potential and challenges of Islamic digital bank operations in Indonesia, focusing on evolving customer experiences. Data was collected from Instagram comments of Bank Aladin Syariah and Bank Jago Syariah, two Indonesian Islamic digital banks, using Apify Instagram comment scrapper and Python. The analysis revealed a predominantly neutral to positive sentiment, indicating the growing success and societal benefits of Islamic digital banks in Indonesia. However, challenges related to technology infrastructure, sharia compliance, and service quality remain. This study offers a novel perspective on the intersection of customer sentiment analysis, Islamic banking, and the Indonesian digital landscape.